2016
DOI: 10.1007/978-981-10-2041-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Fibrosis in ADPKD

Abstract: Diverse signaling pathways have been reported to be associated with polycystic kidney disease (PKD). Cell proliferation is widely known to be an important pathway related to this disease. However, studies on the interactions of inflammation and fibrosis with polycystic kidney disease have been limited. Inflammation is one of the protective systems involved in the response to foreign molecules. In PKD, it was reported that the activity of signaling pathways associated with inflammation is increased. Also, fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…[5][6][7] These cytokines promote fibrosis by activating lamina propria fibroblasts to produce collagen and fibronectin, increasing eosinophil adherence to tissue and enhancing fibroblast contractility. 6,8 Additionally, cross-talk between esophageal epithelial cells and fibroblasts leads to robust fibroblast production of TNF-a, 8,9 a profibrogenic cytokine that has been implicated in fibrotic disease conditions of the liver, intestine, and kidney [10][11][12] ; however, the pathogenic role of TNF-a in patients with EoE remains elusive. In response to these cytokines, stromal fibroblasts are activated to deposit and construct networks of excess collagen and fibronectin in the lamina propria, leading to increased esophageal stiffness.…”
mentioning
confidence: 99%
“…[5][6][7] These cytokines promote fibrosis by activating lamina propria fibroblasts to produce collagen and fibronectin, increasing eosinophil adherence to tissue and enhancing fibroblast contractility. 6,8 Additionally, cross-talk between esophageal epithelial cells and fibroblasts leads to robust fibroblast production of TNF-a, 8,9 a profibrogenic cytokine that has been implicated in fibrotic disease conditions of the liver, intestine, and kidney [10][11][12] ; however, the pathogenic role of TNF-a in patients with EoE remains elusive. In response to these cytokines, stromal fibroblasts are activated to deposit and construct networks of excess collagen and fibronectin in the lamina propria, leading to increased esophageal stiffness.…”
mentioning
confidence: 99%
“…7A). Macrophages surrounding cysts consist of a heterozygous population of M1-like and M2-like macrophages, with the latter of the two thought to promote cyst growth 40,41 . Q-PCR analysis showed that the markers of the pathogenic M2-like macrophages, Arg1 and Mrc1, were decreased by 67.2%%, and 34.9%.…”
Section: Anti-mir-17mentioning
confidence: 99%
“…Therapies currently in clinical trials focus on increased total kidney volume (TKV) as an indicator of disease severity, with decreased TKV reflecting the success of treatment[ 8 - 10 ]. However, an essential feature of the disease is interstitial inflammation and fibrosis[ 11 - 13 ]. Such interstitial changes lead to decreased TKV and strongly correlate with a decline in kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…Renal fibrosis is the key determinant of the progression of all renal disease including ADPKD, irrespective of the original cause, and dictates the eventual outcome[ 11 , 13 , 14 ]. As cystic lesions enlarge, they compress both normal renal parenchyma and vascular elements between multiple cysts, creating a peri-cystic local microenvironment (PLM) that becomes fibrotic over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation